La gestión de las secretarias y su aportación en los eventos empresariales de la Cooperativa de Ahorro y Crédito Juan Pio de Mora de la ciudad de Babahoyo - Aviles Paredes, Xiomara Alejandra (2021)
The following case study was carried out at the Juan Pio de Mora Savings and Credit Cooperative in the city of Babahoyo. The purpose of this study is to analyze in what way the management of secretaries will contribute in the business environment of the cooperative, the problem found was that half of the secretaries who work there do not know in depth about secretarial management and believe that the application of The techniques and skills to have a secretarial management of excellence will not improve, for this reason the study is proposed to let them know that it is important and that it will help efficiently in the development of the work activities of the secretaries. The methodology used in the case study was the deductive method because it is within the same required premises and goes from the particular to the general, the type of descriptive research was also used because it is the one that is responsible for reflecting the characteristics of a population or phenomenon to be investigated, the investigations carried out in this case study are supported by websites, books, magazines and also by personal knowledge found in the development of all the research. It is important to mention that in this study the two variables were analyzed, which are: secretarial management, business events, these two variables will allow us to develop the study and reach the improvement of the problem to benefit the secretaries and the institution.